0265 Respirator fit and face sizes of south african medical laboratory workers: a false sense of protection. (21st August 2017) - Wilson, Kerry; Manganyi, Jeanneth; Rees, David
Abstract : Introduction: Medical laboratory workers (MLWs) are exposed hazardous biological agents; some of which are airborne such as tuberculosis. Respirators despite being a recommended last resort are often the only means of control of exposure to tuberculosis. Aims: the study assessed the adequacy of respirator fit of MLWs and investigated determinants of fit. Methods: 562 medical laboratory workers using respirators underwent quantitative respirator fit testing using the Portacount fit testing machine and their currently supplied respirator. Four facial characteristics were measured on these users by a trained occupational hygienist using callipers and a tape measure. The effect of the independent variables including face dimensions, ethnicity, smoking, respirator make and size, and age group was explored using multiple logistic regressions stratified by sex. Results: A large proportion (78%) of workers failed the fit test. Respirator fit was found to be significantly associated with face length (OR1.04, 95% CI 1.00–1.09), nasal root breadth(OR1.16, 95% CI 1.06–1.28), and respirator shape (cup) (OR0.56, 95% CI 0.39–0.78). Gender was found to be an effect modifier. Discussion: Fit testing and supply of different respirator sizes and types is necessary to protect MLW from airborne hazards. This is particularly important in high incidence tuberculosis settings. Affordable strategies for respirator fit testing and supply of appropriate sizes and types need to be identified for resource-constrained settings.